Computer aided design and characterisation of microstrip low-pass filter/ Rahani Abdullah - Abdullah, Rahani (1997)
The aim of the project is to design, simulate, fabricate and measure the characteristics of a low-pass filter having a cut-off frequency of 4 GHz with a stopband attenuation of 60 dB and a return loss of 20 dB. This project presents the synthesis and design of a generalised Chebyshev low-pass prototype microwave filter. The synthesis of prototype network is done by using Maple V mathematical software and is then simulated and optimized with the aid of a commercially available software called HP-EEsof Libra. It is then fabricated locally in our Fabrication Laboratory on a microstrip circuit. The microstrip laminate has a thickness of 0.8 mm and a dielectric permittivity of 2.35. The filter response is then measured using wiltron 562 Scalar network analyzer.